Influence of Autoantibodies to Estradiol and Progesterone on the Blood Serum Hormones Concentrations in Postmenopausal Healthy Women and Breast Cancer Patients - Glushkov, Andrew N.; G. Polenok, Elena; A. Gordeeva, Lyudmila; A. Mun, Stella; Kostyanko, Mikhail V.; V. Antonov, Alexandr; E. Verzbitskaya, Natalia; A. Vafin, Ilgiz (Asian Pacific Journal of Cancer Biology, 2022)
Background: It is known that antibodies to steroid hormones are associated with some human diseases (systemic lupus erythematosus, thrombosis, recurrent pregnancy loss, autoimmune dermatitis et al.). There were no any data about action of specific autoantibodies on the sex hormones in hormone-dependent cancer patients. Objectives: The purpose of this study was to investigate the probable links between estradiol (Es) and progesterone (Pg) levels and autoantibodies of A-class specific to these hormones (IgA-Es and IgA-Pg) in the blood serum of healthy women and breast cancer patients. Patients and Methods: There were examined 521 nearly diagnosed breast carcinoma patients from Regional Clinical Oncology Dispensary (Kemerovo, Russian Federation) and 143 healthy women from Kemerovo (Russian Federation). The serum concentration of Es and Pg were analyzed by competitive immunoassay using specific monoclonal antibodies. The serum IgA-Pg and IgA-Es were analyzed by solid-phase non-competitive immunoassay using Pg and Es conjugated with bovine serum albumin as adsorbed antigens. The data analysis was performed using software STATISTICA 8.0 (Stat Soft Inc., USA). Results: We discovered that low ratios Pg/Es<4.3 were associated with breast cancer. Personal IgA-Pg/IgA-Es ratios negatively correlated with Es levels and positively correlated with Pg levels and Pg/Es ratios in compared groups. The influence of IgA-Pg/IgA-Es ratio on the hormones levels and their ratio in heathy women was more strong than in breast cancer patients. Conclusions: Our clinical results correspond to the known experimental data about influence of specific antibodies on the levels of steroid hormones in immunized animals. Human autoantibodies to Es and Pg could stimulate or inhibit promotion of carcinogenesis by influence on Pg/Es ratio depending on individual IgA-Pg/IgA-Es ratio.